Histogenesis of human fetal spleen - Sonali Thomas; D N Sinha; A K Singh; Deepa Deopa; Richa Niranjan (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Spleen is the largest secondary lymphatic organ. It acts as a graveyard for RBCs, is essential for immune responses, performs lymphopoiesis in adults and haemopoiesis in fetuses. The present study was conducted to assess the histogenesis of spleen in human fetuses in view of existing literature. Material and Methods: The study was carried out on 34 formalin preserved human fetuses procured from Dr Sushila Tiwari Government Hospital, Haldwani with due clearance from ethical committee. The 6 |jm sections of the spleen were stained with Haematoxylin and Eosin and observed under light microscope. Results: At 14 tol5 weeks, spleen had extensive sinusoids filled with RBCs and few lymphocytes. At 16-18 weeks, trabecular arteries were noticed more towards centre along with extensive haemopoietic cells in the venous sinusoids. By 20th week lymphocytic aggregation had started around arterioles. By 24 weeks periarteriolar lymphatic sheath was clearly observed. At term (37-40 weeks), classical primary lymphoid follicle was present but germinal centers were not observed. Conclusion: During earlier differentiation, spleen symbolizes the function of haemopoietic activities and gradually during subsequent gestation; it establishes its identity as a principle lymphoid tissue.